KONSEP PENDIDIKAN BERBASIS EKSPERIMEN DALAM QS. AL-BAQARAH AYAT 260 DAN RELEVANSINYA DALAM PEMBELAJARAN ANAK - Nada Ramadhania; Rafika Yuli; Hidayatullah Ismail (Al-ATHFAL: Jurnal Pendidikan Anak, 2026)
This study aims to analyze the concept of experimental-based education in the Qur’an, particularly in Surah Al-Baqarah verse 260, and to examine its relevance to modern education. This research employs a qualitative approach using library research methods, with data collected from classical and contemporary tafsir, educational theories, and recent scholarly studies. The results show that the concept of experiment in this verse is reflected through a learning process involving direct experience, observation, and empirical verification, as demonstrated in the dialogue between Prophet Ibrahim and Allah. This indicates that experimental learning plays an important role in strengthening understanding and belief. Furthermore, this concept is relevant to modern educational approaches that emphasize active participation and reflective processes. Therefore, experimental-based education in the Qur’an provides a conceptual foundation for developing active and contextual learning models in contemporary Islamic education.